2020
DOI: 10.1007/s10900-020-00887-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health and Risk of SARS-CoV-2 Infection in Community-Dwelling Older Adults Living in a Rural Latin American Setting

Abstract: High social risk, as measured by the social determinants of health (SDH), may increase the risk of SARS-CoV-2 infection. However, this association has not been studied in rural communities. Using the Atahualpa Project cohort, we aimed to assess the association between SDH and SARS-CoV-2 seropositivity in community-dwelling older adults living in rural Ecuador. SARS-CoV-2 antibodies were determined in 319 individuals aged ≥ 60 years that completed a validated field instrument to assess their social risk before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
1
27
0
1
Order By: Relevance
“…found that poor quality of life in the cancer survivors was also noticed in residents living in the highly segregated black counties. Del Brutto et al 74 . found that in rural communities of Ecuador, for each unit increase in social risk measured by the Gijon scale, the infection rates of COVID‐19 increased by 15%.…”
Section: Discussionmentioning
confidence: 99%
“…found that poor quality of life in the cancer survivors was also noticed in residents living in the highly segregated black counties. Del Brutto et al 74 . found that in rural communities of Ecuador, for each unit increase in social risk measured by the Gijon scale, the infection rates of COVID‐19 increased by 15%.…”
Section: Discussionmentioning
confidence: 99%
“…This problem has also been anticipated in Brazilian aborigines living in closed communities, since they will be forced to travel to highly infected cities to receive a compensatory monetary bonus from the government [8]. To the immunological naivete of these populations, it must be added the adverse circumstances in which they live regarding inadequacy of control measures, poor social determinants of health and inadequate access to medical care [13]. Rural communities of Latin America do not seem to be prepared for this situation, and will likely be one of the hot spots of this pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in Atahualpa, a remote rural village in coastal Ecuador, where previous studies on SARS-CoV-2 infection have been conducted [9,[11][12][13]. Characteristics of Atahualpa residents have been described elsewhere [14].…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Center for Disease Control and Prevention (CDC) provides a taxonomy for SDoH that is comprised of 6 domains: economic stability (e.g., income), education (e.g., educational attainment and graduation rates), health and healthcare access ( access to health and how well an individual or group understands the health information to make the appropriate decisions), social and community context (variables reflect the social setting that an individual resides and their community involvement), demographics (e.g., race/ethnicity, sex, age), and neighborhood and built environment (variables that relate to the physical surrounding environment and have the potential to overlap other domains) [8,9]. SDoH are associated with COVID-19 transmission and mortality [10][11][12][13][14][15][16][17]. SDoH overlap and interact in real-world setttings, requiring careful disentanglement of their individual downstream inpact on health outcomes such as COVID-19 spread.…”
Section: Social Determinants Of Covid-19mentioning
confidence: 99%